2021
DOI: 10.1177/0300060520987395
|View full text |Cite
|
Sign up to set email alerts
|

Awake fiberoptic orotracheal intubation: a protocol feasibility study

Abstract: Objective To assess the feasibility of an awake fiberoptic intubation (AFOI) protocol. Methods We enrolled 40 patients with simulated difficult intubation. The protocol consisted of conscious sedation (midazolam, 0.03 mg/kg and sufentanil, 0.1 µg/kg), regional anesthesia, and intubation. The time, first-attempt intubation success rate, hemodynamic parameters, blood oxygen saturation (SpO2), intubation amnesia rate, patient satisfaction, and relative complications were recorded. Results AFOI was completed in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although there have been few clinical trials, our results are basically similar to previous studies. Ma et al 40 reported that the hemodynamic parameters and respiration remained stable in awake fibreoptic orotracheal intubation under SLN block. In a prospective randomized clinical study, Ambi et al 26 showed that HR and MAP were significantly more stable in the ultrasound group.…”
Section: Discussionmentioning
confidence: 98%
“…Although there have been few clinical trials, our results are basically similar to previous studies. Ma et al 40 reported that the hemodynamic parameters and respiration remained stable in awake fibreoptic orotracheal intubation under SLN block. In a prospective randomized clinical study, Ambi et al 26 showed that HR and MAP were significantly more stable in the ultrasound group.…”
Section: Discussionmentioning
confidence: 98%
“…Flexible bronchoscope-guided intubation can be performed nasally or orally in awake patients with topical or regional anesthesia alone, or in sedated or anesthetized patients. The nasal route is often used on patients with poor mouth opening or a large tongue as it courses past the nasopharynx with less obstruction by the tongue [ 21 ]. Awake flexible bronchoscope-guided intubation is strongly recommended in patients with anticipated difficult airways [ 2 , 6 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might exacerbate intubation difficulty and eventually increase the risk of hypoxia in patients whose airways are difficult to manage 4 . Therefore, awake tracheal intubation (ATI) is the gold standard for such patients 8 . The Difficult Airway Society recommended supplemental oxygen during ATI at the Grade B level 9 .…”
Section: Introductionmentioning
confidence: 99%